A Manipulation of Semantic Meanings as a Humor Construction Strategy - Romadlani, Muhammad Masqotul Imam (Universitas Negeri Semarang, 2021)
This research is conducted to reveal how humorous utterances are constructed by manipulating semantic meaning especially dealing with lexical semantics. Lexical semantics provides multiple meanings that portray their meaningsÃ¢â‚¬â„¢ relationship among a word and they are potentially exploited to elicit humor. This research examines utterances manipulating lexical semantics as the strategy of humor creation inÃ‚Â Mind Your LanguageÃ‚Â situation comedy. Applying a descriptive qualitative approach, the findings indicate that five types of lexical semantics are utilized as strategies of humorous utterances creation. Those types of lexical semantics are polysemy, homonymy, homophone, hyponymy, dan synonymy. Because of their multiple relation meanings, the speaker can refer to other meanings to construct different meanings with the hearer. The speaker constructs an incongruent meaning between what the hearerÃ¢â‚¬â„¢s perception is and what the speaker meant. The deviation of lexical semantics between the hearer and the speaker completely illustrates the concept of incongruity theory of humor.Ã‚Â